NEUTROSOFIK LIMIT DAN PENGHITUNGANNYA - Suryoto, Suryoto (MATEMATIKA, 2016)
Neutrosophic limit means the limit of a neutrosophic function. This article discusses the neutrosophic limit and the algebraic aspects related, including neutrosophic function, neutrosophic mereo-limit, neutrosophic limit and itâ€™s calculation. The rules and the calculation method of neutrosophic limit similar to the rules and the method for calculating the classical limit, only the role of independent variables in the classical limit is taken over by a closed interval which is a subset of the set of real numbers.Â